Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Chain rule states that $$\frac{df}{dx} \frac{dx}{dt} = \frac{df}{dt}$$.

Suppose that $f$ is function $f(x,y)$. In this case, would normal chain rule still work?

share|improve this question
    
Read this, please. –  Frank Science Feb 4 '13 at 6:18

1 Answer 1

up vote 3 down vote accepted

The multivariable chain rule goes like this:

$$ \frac{df}{dt} = \frac{\partial f}{\partial x}\cdot \frac{dx}{dt}+ \frac{\partial f}{\partial y}\frac{dy}{dt} $$ If you can isolate for $\dfrac{dy}{dx}$, then you can always just do implicit differentiation.

Let's do an example: $$ f=f(x,y) = x^2 - y $$ Where $$ x(t) = t, \; \; y(t) = t $$ $$ \frac{df}{dt} \frac{df}{dx} \cdot \frac{dx}{dt} = 2x -\frac{dy}{dx}\frac{dx}{dt}= 2t - 1 $$ Also $$ \frac{df}{dt} = \frac{\partial f}{\partial x}\cdot \frac{dx}{dt}+ \frac{\partial f}{\partial y}\frac{dy}{dt} = 2x - 1 = 2t - 1 $$ Now let's do the same example, except this time: $$ f=f(x,y)= x^2 - y\\ x(t)=t\ln(t), \;\; y(t) = t\sin(t) \\ \Rightarrow \frac{df}{dt} = 2t\ln(t)(\ln(t) + 1) -(\sin(t) +t\cos(t)) $$ Would implicit differentiation work here? Yes. But it requires more steps.
Implicit differentiation would be the inefficient route as, $$ e^{x/t} = t \Rightarrow y= e^{x/t}\sin(t) \Rightarrow \frac{dy}{dt} = \frac{dy}{dx}\frac{dx}{dt} = \\ \left(\frac{1}{t}\frac{dx}{dt}-\frac{x}{t^2}\right)e^{\frac{x}{t}}\sin(t)+e^{\frac{x}{t}}\cos(t) = \\ e^{\frac{x}{t}}\left(\left(\frac{1}{t}\frac{dx}{dt}-\frac{x}{t^2}\right)\sin(t)+\cos(t)\right) =\\ t\left(\frac{\ln(t)+1}{t} - \frac{t\ln(t)}{t^2}\right)\sin(t) + t\cos(t) = \\ \left(\ln(t) +1 - \ln(t)\right)\sin(t) + t\cos(t) = \\ \sin(t)+t \cos(t) $$ But it still works out.

You can check out this site:
Link
For examples.

share|improve this answer
    
yes I know this; but can we use just ordinary chain rule instead of multivariable chain rule? –  Lanz Feb 4 '13 at 5:43
    
No, actually, your calculation of $\frac{df}{dx} \cdot \frac{dx}{dt}$ is wrong - thinking of $df/dx$ is $(2x-dy/dx)$ and as $dy/dx = 1$ and $dx/dt = 1$, we get the same answer $2t-1$... –  Lanz Feb 4 '13 at 6:04
    
but $x=y=t$. Look, they must be 1. –  Lanz Feb 4 '13 at 6:09
    
@Lanz I have updated the example. –  Rustyn Feb 4 '13 at 8:08
    
Thanks very much! –  Lanz Feb 4 '13 at 8:09

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.